The Camouflage That Grapples Our Perception - Luqman Hakim, Ahmad Shah (Faculty of Mechanical & Automotive Engineering Technology, 2021)
During World War 2, airplanes designers and engineers were researching on how to best strengthen their warplanes so that it won’t doom easily as a result of enduring the multitude hits from the enemy’s planes.